Low frequency plasma turbulence excited by cometary ions - Lakhina, G.S. (My University, 1988)
Properties of the hydromagnetic turbulence observed near comet Halley are explained by a model consisting of a gas of Alfven solitons generated via the modulational instability of large amplitude Alfven waves excited by picked up cometary ions. The lower hybrid instability excited by the cometary ions' distribution can explain the 0 - 300 Hz electrostatic noise observed near comet Halley.
Keywords: Hydromagnetic; Alfven waves; Cometary ions; Plasma turbulence